Lack of grading agreement among international hemostasis external quality assessment programs. Issue 1 (January 2018) - Olson, John D.; Jennings, Ian; Meijer, Piet; Bon, Chantal; Bonar, Roslyn; Favaloro, Emmanuel J.; Higgins, Russell A.; Keeney, Michael; Mammen, Joy; Marlar, Richard A.; Meley, Roland; Nair, Sukesh C.; et al.
Abstract : N/A: Laboratory quality programs rely on internal quality control and external quality assessment (EQA). EQA programs provide unknown specimens for the laboratory to test. The laboratory's result is compared with other (peer) laboratories performing the same test. EQA programs assign target values using a variety of methods statistical tools and performance assessment of 'pass' or 'fail' is made. EQA provider members of the international organization, external quality assurance in thrombosis and hemostasis, took part in a study to compare outcome of performance analysis using the same data set of laboratory results. Eleven EQA organizations using eight different analytical approaches participated. Data for a normal and prolonged activated partial thromboplastin time (aPTT) and a normal and reduced factor VIII (FVIII) from 218 laboratories were sent to the EQA providers who analyzed the data set using their method of evaluation for aPTT and FVIII, determining the performance for each laboratory record in the data set. Providers also summarized their statistical approach to assignment of target values and laboratory performance. Each laboratory record in the data set was graded pass/fail by all EQA providers for each of the four analytes. There was a lack of agreement of pass/fail grading among EQA programs. Discordance in the grading was 17.9 and 11% of normal and prolonged aPTT results, respectively, and 20.2 and 17.4% of normal and reduced FVIII results, respectively. All EQA programs in this study employed statistical methods compliant with the International Standardization Organization (ISO), ISO 13528, yet the evaluation of laboratory results for all four analytes showed remarkable grading discordance. Abstract : Supplemental Digital Content is available in the text